The Visual Formation and Theocratic Narrative of the Sanxingdui Bronze Deity Statue with Protruding Eyes - Shan Chen; Jingyi Chen (Comparative Literature: East & West)
Academic definitions of the Sanxingdui bronze mask with protruding eyes as a “mask” are limited. From design and semiotic perspectives, this study proposes its essence may be that of an independent, bodiless deity statue. Research indicates this deity statue employs “pointed ears and protruding eyes” as its core symbols, constructing divine signifiers like the “geometric gaze” through surreal forms. The piece-molding technique and the “bronze face/clay-wooden body” materiality metaphorically represent the dialectical relationship between the “sacred and the profane.” It establishes a hierarchical structure of “top-middle-base levels” through its pictorial genealogy and spatial arrangement, while its bodiless form further intensifies the transcendence of divinity. Cross-civilizational comparisons reveal it breaks from traditional anthropomorphic expressions, forming a paradigm of “impersonal divinity.” In ritual practice, it forms a dual mechanism of “static ontology – dynamic medium” with wearable masks, jointly materializing the construction of theocratic beliefs. This study provides a new analytical dimension for research on divine expression in early civilizations.